2016
DOI: 10.1103/physrevb.93.205439
|View full text |Cite
|
Sign up to set email alerts
|

Towards nanoscale multiplexing with parity-time-symmetric plasmonic coaxial waveguides

Abstract: We theoretically investigate a nanoscale mode-division multiplexing scheme based on parity-time (PT ) symmetric coaxial plasmonic waveguides. Coaxial waveguides support paired degenerate modes corresponding to distinct orbital angular momentum states. PT symmetric inclusions of gain and loss break the degeneracy of the paired modes and create new hybrid modes without orbital angular momentum. This process can be made thresholdless by matching the mode order with the number of gain and loss sections within the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 41 publications
(112 reference statements)
0
7
0
Order By: Relevance
“…EPs of this kind may be studied experimentally, and there is a rapidly increasing number of studies related to fundamental science and technology. For example, there are studies with pump-induced lasers [7,8], microwave cavities and wires [9][10][11][12][13][14][15][16][17], LRC circuits [18], exciton-polariton billiards [19], and more [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…EPs of this kind may be studied experimentally, and there is a rapidly increasing number of studies related to fundamental science and technology. For example, there are studies with pump-induced lasers [7,8], microwave cavities and wires [9][10][11][12][13][14][15][16][17], LRC circuits [18], exciton-polariton billiards [19], and more [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…[89,90] Some recent works propose to exploit PT symmetric concepts in plasmonic devices, for example, active polarization control of light using coaxial PT nanoplasmonic structure, [226] multiplexing in coaxial plasmonic waveguides. [227] Despite the significant possibilities of PT related ideas in plasmonics, its practical implementation requires precise manipulation in the distributions of the gain-loss elements at subwavelength scale, which might be difficult at times. So, accessing EP physics in general plasmonic systems can be challenging.…”
Section: Metamaterials and Plasmonicsmentioning
confidence: 99%
“…In a previous work, we showed that these eigenvalues correspond to modes localized to the gain and loss sections in the coaxial waveguide, with near-linear polarization distributions. 46 Because only the imaginary part of the channel refractive index is modulated, the resonance wavelength changes by less than a nanometer-a distinct advantage of this design over alternate phase-change material approaches. Although we report our findings for a specific wavelength with a specific geometry, future devices could easily be tailored across a wide spectral range by varying the dielectric channel thickness, the core diameter, and the aperture's length.…”
Section: Transmission Of the Pt -Symmetric Coaxial Resonatormentioning
confidence: 99%
“…The location of the EP in parameter space is controlled by the degree of non-Hermiticity and geometry. While a finite amount of loss and gain is generally required to reach an EP, recent designs based on modal degeneracy and temporal variation can enable thresholdless operation [45][46][47][48] . These distributions help PT -symmetric systems become realizable with physical values of gain and loss, and they are fully leveraged in the coaxial geometry under investigation in this work.…”
Section: Introductionmentioning
confidence: 99%